CURRENT ISSUES OF ARRANGING POST-GRADUATE EDUCATION FOR ACADEMIC STAFF TRAINING - Petr I. Kasatkin; Maxim I. Inozemtsev (Высшее образование в России)
The article discusses most pressing issues of arranging post-graduate educational process for academic staff training at the present stage. The arrival of the new Federal State Educational Standards ofhigher education prompts more acceptable solutions to problems facing educational organizations. Special attention is paid to working out post-graduate courses of double training with international partner universities to make it possible for the national educational organizations to join on equal terms the world's academic community.